O ensino domiciliar na produção acadêmica (2013 - 2022) - Gomes, Camila de Souza (2024)
This work, linked to the Research Line Fundamentals of Educational Processes of PPGE/FE/UFG, investigates homeschooling with the objective of understanding how the connection between economic and political processes and the defense of homeschooling is effective in times of advancement of neoliberal and neoconservative propositions in Brazil. To capture the economic and political links in their reciprocal relations with school educational processes, the work is grounded in the studies of Marx (2004; 2010; 2023), Marx and Engels (1998), Hobsbawm (1982), Ianni (1988), Netto and Braz (2012), Saviani (2015), Miranda (2020), Lopes (1981), Ricci (2022), and Cury (2000; 2014; 2017; 2018; 2019). Through theoretical and bibliographic study (Lima; Mioto, 2007), legislation regarding the topic, as well as theses and dissertations deposited in the Brazilian Digital Library of Theses and Dissertations from 2013 to 2022 were analyzed. The results indicate, within the scope of Congress, that the defense of homeschooling in the Brazilian legislature is tied to neoliberal and neoconservative agendas, with an attempt to dismantle what is mistakenly considered the State's monopoly on education. As a counterpoint, it proposes the transfer of responsibility and educational decisionmaking from the public to the private sphere. Regarding the analysis of theses and dissertations, the field of Education shows a greater number of research studies on the topic, followed by the field of Law. It was found that there is a higher prevalence of unfavorable works towards homeschooling in research originating from the educational area, emphasizing the social role of public schools; the studies from the field of Law, despite some reservations, are proactive, focusing on the regulation of homeschooling. The material and objective conditions that create tension and criticize the role of public schools indicate that there must be a sustained accurate reflection on the topic. Lastly, the analysis of the works reveals that schools are permeated by political, economic, and ideological issues and are spaces of dispute, demonstrating the need to continually renew the defense of the principles of public, secular, compulsory education committed to critically oriented formation.